Supplementation of guanidinoacetic acid in feed with different levels of protein on intestinal histomorphology, serum biochemistry, and meat quality of broiler - D. Rahmawati; C. Hanim (Journal of the Indonesian Tropical Animal Agriculture, 2022)
This study aimed to investigate the effect of guanidinoacetic acid (GAA) with different protein levels in feed on intestinal histomorphology, serum biochemistry, and meat quality of broiler chicken. GAA is the only direct precursor of creatine and is involved in the synthesis of bioenergy cellular. This research used 1.176 day-old chicks of the Lohmann Indian River strain that were reared for 35 days. The supplementation effect was investigated using six treatments, i.e., two levels of feed protein and three levels of GAA, with seven replications. Broiler chickens were fed with 23% and 21% crude pro-tein during the pre-starter phase, 21% and 19% during the starter phase, and 19% and 17% during the finisher phase, with a GAA addition of 0 g/ton, 600 g/ton, and 1200 g/ton, respectively. The result showed GAA supplementation with different protein levels reduced triglyceride (P<0,05), cholesterol levels in serum (P<0,05), increased surface area of the microvilli (P<0,05), pH of breast meat (P<0,05), but did not affect the chemical quality of breast meat (P>0,05). In conclusion, GAA supplementation in different level protein diets increased the surface area of the microvilli, pH of breast meat, reduce se-rum cholesterol and triglycerides, without affecting the chemical quality of broiler meat.